2007
DOI: 10.2522/ptj.20050237
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Comprehensive International Classification of Functioning, Disability and Health Core Set for Rheumatoid Arthritis: The Perspective of Physical Therapists

Abstract: The validity of the ICF Core Set for RA was largely supported. However, some categories currently not covered by the ICF Core Set for RA will need to be investigated further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 42 publications
2
16
0
1
Order By: Relevance
“…However, they warned readers that different hierarchical log-linear models indicated that the strength of agreement was not homogenous (34). Kirchberger et al (35) investigated the validity of the ICF core sets for rheumatoid arthritis from a physiotherapist's perspective. They stated that the validity of the core set was largely supported but that some categories currently not covered will need further investigation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they warned readers that different hierarchical log-linear models indicated that the strength of agreement was not homogenous (34). Kirchberger et al (35) investigated the validity of the ICF core sets for rheumatoid arthritis from a physiotherapist's perspective. They stated that the validity of the core set was largely supported but that some categories currently not covered will need further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…The ICF provides a universal and standardized language, which is also comprehensible for patients (33). It offers a framework regarding disability that goes beyond mere disease (35) Á the possibility to medically classify functioning without being a psychometrically sound measure (34). The ICF promises the opportunity to compare collected data (33,37).…”
Section: Basic Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the core set for stroke, only 25% of concepts used are environmental factors. In addition, further studies have emphasized the need to consider all ICF components (26,27). The ICF-A can be regarded as such an example and be considered as a tailor-made assessment based on the ICF for occupational therapists (2,7).…”
Section: Discussionmentioning
confidence: 99%
“…In einer qualitativen Studie wurde basierend auf Interviews mit Patienten mit rheumatoider Arthritis die Validität des ICF Core Sets für rheumatoide Arthritis aus Patientenperspektive untersucht[19]. Die Validität aus der Perspektive von Physiotherapeuten und Ergotherapeuten wurde in Expertenbefragungen über mehrere Runden unter Verwendung der Delphi-Technik beurteilt[14,15]. In diesen Studien konnte die Validität der ICF Core Sets weitgehend bestätigt werden.…”
unclassified